Effectivity of convex triangular and rectangular cross section instruments on decreasing the amount of root canal enterococcus faecalis bacteria colonies - Meilina Goenawan; Juni J. Nugroho; Christine R. Anastasia; Aries C. Trilaksana; Nurhayaty Natsir; Andi Sumidarti (DiscoverSys Inc., 2016)
This study aims to evaluate effectiveness difference between convex triangular and rectangular cross section rotary instruments on root canal Enterococcus faecalis bacteria colonies. Samples mandibular premolar teeth with one narrow and straight root canal divided into 3 groups : instrumented with convex triangular cross section rotary instruments, rectangular cross section rotary instruments, and convex triangular cross section manual instruments. Each group consisted of 9 samples. Standardized teeth length, instrumented to #15 K-file and sterilized. E. faecalis suspension in BHIB was standardized then 27 root canals contaminated. Root canals were incubated for 21 days. Every 48 hours root canals added with BHIB. Initial samples were collected, plated in agar culture medium and incubated for bacterial count. and then bacterial count was performed again. Data were collected and analysed using Paired T-test and ANOVAThe results showed there are significant difference on Enterococcus faecalis bacteria colonies amount before and after preparation with all instruments that was used and bacterial reduction amount in root canals were greater on convex triangular cross section instruments than on rectangular cross section instruments even there was no significant difference.